The Carolina Population Center Family Planning Administrator Training Game - Moreland, R. Scott; Chu, Kong; Jacobson, Edward; Naylor, Thomas H. (Management Science, 1972)
This role-playing game for family planning administrators is a technique for the learning of effective planning and rational allocation of economic resources of population control programs. Through the use of electronic data processing, the game provides valuable experience in the sort of decision making that public health officials seldom encounter before going into the field. The game simulates an environment in which the family planning administrator' must make his allocation decisions and from which he receives feedback in the form of demographic results. The game may be made to react to simulate a particular country if the game leader has access to the relevant data, thus providing preparation for decisions in the field.